1992
DOI: 10.1016/0014-5793(92)80766-a
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum inhibits neurofilament protein degradation by multiple cytoskeleton‐associated proteases

Abstract: The environmental ncurotoxin aluminum exerts several distinct biochemical effects on neurofilament proteins, including subunit agg~gation, disruption of the normal segregation of phospho~lated subunits within axons leading to abnormal perikaryal accumulation, and inhibition of in vitro degradation by the calcium-dependent neutral protease0 ealpain. In the present study, we demonstrate that exposure of mouse CNS cytosk~letal preparations to aluminum chloride inhibits the degradation of neurofilament proteins by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
(43 reference statements)
1
12
0
3
Order By: Relevance
“…However, the microtubules in these tissues became increasingly stabilized and resistant to depolymerization after Al application. This is similar to in vitro reports in mammalian systems demonstrating that Al binding to microtubules and neurofilaments can significantly delay their depolymerization (MacDonald et al, 1987;MacDonald and Martin, 1988;Nixon et al, 1990;Shea et al, 1992). The stabilizing effect of Al on the microtubules of cells on the outer cortex was demonstrated by our auxin experiments, which showed that even 1 h of Al exposure could block the IAA-induced reorientation of microtubules from transverse to longitudinal arrays.…”
Section: Discussionsupporting
confidence: 76%
“…However, the microtubules in these tissues became increasingly stabilized and resistant to depolymerization after Al application. This is similar to in vitro reports in mammalian systems demonstrating that Al binding to microtubules and neurofilaments can significantly delay their depolymerization (MacDonald et al, 1987;MacDonald and Martin, 1988;Nixon et al, 1990;Shea et al, 1992). The stabilizing effect of Al on the microtubules of cells on the outer cortex was demonstrated by our auxin experiments, which showed that even 1 h of Al exposure could block the IAA-induced reorientation of microtubules from transverse to longitudinal arrays.…”
Section: Discussionsupporting
confidence: 76%
“…Despite many reviews stating that Al may occupy enzymatic metal binding domains [1,3,5,[31][32][33] little or no evidence to support this. Of the results presented to date on the inhibition of enzyme activity by Al, inhibition via binding of Al to the substrate is rarely if ever considered.…”
Section: It Is Likely That Almentioning
confidence: 99%
“…In any case, aluminum salt irreversibly inactivated calpain but only at high aluminum concentrations (IC 50 0/1.2 and 2.1 mM for aluminum lactate and AlCl 3 , respectively), although a longer exposure to the ion reduced by twofolds the level required for protease inhibition. The interaction of aluminum with neurofilament proteins and the effects on their proteolysis [12], suggest possible mechanisms for the impaired axoplasmic transport of neurofilaments and their accumulation in neuronal perikarya after aluminum absorption 'in vivo'. Other studies confirmed these results: in the presence of millimolar concentrations of Ca 2' calpain I was inhibited by submillimolar concentrations of aluminum ion (IC 50 0/100 mM); but in the millimolar range aluminum ion was a less effective inhibitor and the activity of the enzyme reached about 65% (at a concentration of aluminum of 10 mM) of the control activity assayed without aluminum.…”
Section: Effect Of Aluminum On the Binding Properties Of Calpainsmentioning
confidence: 99%
“…Aluminum salts may induce phosphorus depletion, which however is generally not severe, even though a prolonged administration of large doses may bring about hypophosphatemia, especially in patients with inadequate dietary intake of phosphorus; in these patients, hypercalciuria results as a secondary effect to bone resorption and increased intestinal absorption of calcium [10]. Intracranial administration of aluminum salts to cats, rabbits and dogs induces intraneuronal accumulations of neurofibrillary consisting of 10 nm intermediate filaments [11,12] in perikarya and proximal axons which closely resemble neuronal alterations at the early stages of amyotrophic lateral sclerosis (ALS) and share some features with the neuronal lesions in the ALS-Parkinson dementia complex of Guam [8,13,14]. Aluminum at non-toxic doses is thought to be also involved in different diseases: in fact, excessive dietary aluminum has been proposed to be a factor contributing to several neurological disorders in humans.…”
Section: Introductionmentioning
confidence: 99%